On capturing the grain-scale elastic and plastic anisotropy of alpha-Ti with spherical nanoindentation and electron back-scattered diffraction. (15th September 2016) - Weaver, Jordan S.; Priddy, Matthew W.; McDowell, David L.; Kalidindi, Surya R.
Abstract: Spherical nanoindentation combined with electron back-scattered diffraction has been employed to characterize the grain-scale elastic and plastic anisotropy of single crystal alpha-Ti of two different compositions (in two different titanium alloys). Data analyses protocols needed to reliably extract the desired properties of interest are extended and demonstrated in this paper. Specifically, the grain-scale mechanical response is extracted in the form of indentation stress-strain curves for commercially pure (CP-Ti) alpha-Ti and alloyed (Ti-64) titanium from measurements on polycrystalline samples. The results are compared with responses of single crystals and nanoindentation tests (hardness and modulus) from the literature, and the measured indentation moduli are validated using crystal-elastic finite element simulations. The results obtained in this study show that (i) it is possible to characterize reliably the elastic and plastic anisotropy of alpha-Ti (hcp) of varying alloying contents with spherical nanoindentation stress-strain curves, (ii) the indentation modulus of alpha-Ti-64 is 5–10% less than CP-Ti, and (iii) the indentation yield strength of alpha-Ti-64 is 50–80% higher than CP-Ti. Graphical abstract: